2008
DOI: 10.1037/0022-006x.76.4.531
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient interventions for adolescent substance abuse: A quality of evidence review.

Abstract: Previous reviews of outpatient interventions for adolescent substance abuse have been limited in the extent to which they considered the methodological quality of individual studies. The authors assessed 31 randomized trials of outpatient interventions for adolescent substance abuse on 14 attributes of trial quality. A quality of evidence score was calculated for each study and used to compare the evidence in support of different outpatient interventions. Across studies, frequently reported methodological attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(158 citation statements)
references
References 89 publications
4
146
0
8
Order By: Relevance
“…Tripodi and Bender (2011) reviewed 10 treatment studies examining alcohol or marijuana outcomes in samples of juvenile offenders and concluded that FBTs and individual-based treatments had similar, small-to-moderate effects on ASU outcomes. A review by Becker and Curry (2008) took the additional step of systematically rating the methodological rigor of ASU treatment studies (see also Calabria, EVIDENCE BASE UPDATE ASU Shakeshaft, & Havard, 2011) to generate quality-ofevidence data on each. They devised 14 specific quality attributes compiled primarily from CONSORT (Moher, Schultz, & Altman, 2001) and Methodological Quality Rating Scale (W. R. Miller et al, 1995) criteria.…”
Section: Summary Of Waldron and Turner 2008 Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tripodi and Bender (2011) reviewed 10 treatment studies examining alcohol or marijuana outcomes in samples of juvenile offenders and concluded that FBTs and individual-based treatments had similar, small-to-moderate effects on ASU outcomes. A review by Becker and Curry (2008) took the additional step of systematically rating the methodological rigor of ASU treatment studies (see also Calabria, EVIDENCE BASE UPDATE ASU Shakeshaft, & Havard, 2011) to generate quality-ofevidence data on each. They devised 14 specific quality attributes compiled primarily from CONSORT (Moher, Schultz, & Altman, 2001) and Methodological Quality Rating Scale (W. R. Miller et al, 1995) criteria.…”
Section: Summary Of Waldron and Turner 2008 Reviewmentioning
confidence: 99%
“…Type 2 studies are defined as comparative studies in which some Type 1 criteria are missing, but the study is not fatally flawed (note that the 11 inclusion criteria just described automatically eliminated studies that did not qualify as at least Type 2). To create more reliable standards, the Nathan and Gorman criteria were further operationalized as follows, incorporating attributes for judging methodological quality derived from Becker and Curry (2008): (a) Random assignment: as reported in the study; (b) Blind assessment: presumed true or near-true unless reported otherwise; (c) Inclusion and Exclusion criteria: adequately described sample selection procedures and demographic and clinical characteristics; (d) Strong ASU measurement: used a calendar-based or objective measure of SU; (e) Sample size: at least 49 participants per condition, 1 or, power justification is specifically described; (f) Follow-up duration: 6 months or longer; (g) Statistical analysis: used intent-to-treat analyses, reported between-group effect sizes for ASU, and used methods adequate to examine change over time.…”
Section: Quality-of-evidence Categories For the Study Poolmentioning
confidence: 99%
“…ex., approche de réduction des méfaits). Les thérapies familiales systémiques, les approches cognitivo-comportementales et les traitements en groupe de pairs ont reçu des preuves empiriques solides de leur efficacité (Becker & Curry, 2008;Dyer 2006;Liddle, Dakof, Turner, Henderson, & Greenbaum, 2008).…”
Section: Les Déficits Neuropsychologiques Associés à L'abus De Psychounclassified
“…Les services offerts durant le traitement de la toxicomanie chez les adolescents reposent sur des approches diverses : familiale, cognitive-behaviorale, Minnesota en 12 étapes, motivationnelle, et milieu de vie thérapeutique (Becker & Curry, 2008;Brunelle, Landry & Bertrand, 2008;Kaminer & Burleson, 1999;Waldron & Turner, 2008).…”
Section: Les Principales Formes De Traitement De La Toxicomanieunclassified